ANALISIS LAPORAN KEUANGAN PADA UMKM DI KARAWANG, JAWA BARAT - Bachtar Bakrie; Parlis Lawalata; Andre Depeda; Gita Febrina; Josinta A Kau (Sekolah Tinggi Pariwisata Mataram, 2022)
Micro, Small, and Medium Enterprises (MSMEs) in Tegalsari Village, Karawang Regency, West Java, have existed and run for a long time. However, there are still many problems experienced by the MSME actors in running their businesses. Some of the main difficulties experienced are problems in making business licenses, marketing, and business capital problems. The most dominant problem here is capital, where entrepreneurs constantly lack sufficient money to run a business. From the above issues, it becomes a reference for the University of Respati Indonesia (URINDO) to carry out Community Service (PKM) activities held by lecturers and students of Semester II Master Program of Study Program of Business Administration. The main objectives of this activity are 1). To assist MSME actors in answering the problems they experienced above, 2). To help the MSMEs manage good financial management to solve capital problems encountered. Conclusions from the implementation of PKM activities for MSMEs in Tegalsari Village, Karawang Regency, West Java are 1). PKM activities in which material delivery on financial management are not crucial for MSME actors in Tegalsari Village, Kecamatan Karawang, West Java. The participation of the participants from the beginning of the activity to the end is very beneficial for the participants in the implementation of business development. 2). Mentoring and training activities for MSME actors in the preparation of simple financial statements according to the stages that are young and understood to be very influential for MSME actors in increasing knowledge, understanding, and skills in preparing their business financial statements, to be able to know the financial performance of the business, as well as to give direction in developing their business.